Survey of Non-Cash Food Aid Users in East Banjarmasin District - Singgih Priono; Septeria Noor Yuliannisa; Bakhtiar; Muhammad Jamili; Ali Khamdan (stiatabalong.ac.id, 2022)
Non-cash Food Aid Users (BPNT) is food aid from the government that is given to Beneficiary Families (KPM) every month through an electronic account mechanism which is used only to buy food at E-Warong (Electronic Mutual Cooperation Stalls). In Presidential Regulation Number 63 of 2017 that the Indonesian people who get BPNT are people who are classified as poor even though in its implementation there are many things that do not match the amount of assistance with the basic needs of the community so that this assistance is complained of by the community. This research, entitled